If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + (3 + b) = 0 Remove parenthesis around (3 + b) 10 + 3 + b = 0 Combine like terms: 10 + 3 = 13 13 + b = 0 Solving 13 + b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + b = 0 + -13 Combine like terms: 13 + -13 = 0 0 + b = 0 + -13 b = 0 + -13 Combine like terms: 0 + -13 = -13 b = -13 Simplifying b = -13
| 8x-4x+3=8 | | 3z/7-7=4 | | -37=8x+3 | | 6=-2r-2 | | 6.5x=24 | | 17*(ab)= | | p(x)=3x^4-2x^2-x+2 | | 4y-4+4y-8= | | w/5-3=4 | | 2x+265=1000 | | 4+3w=10 | | 7i=12 | | 23-2b=7 | | 15-3t=6 | | 5(4x-6)-2(2x+1)=3(-3x-2) | | 8+3h=20 | | 3x+2.50=135.97 | | 14=4q+10 | | y+40=9y | | g(7/3)=7-3y | | 3x+4.85=8.40 | | 3=9-2v | | 3g+4=-11 | | 7=2t+1 | | 6x+4.60=8.40 | | 3=1/2x-1 | | 10z/8/6 | | 3x+40=612.06 | | 10z/8=6 | | 2x+45=61.24 | | X=QSV | | 20x+600=1260 |